2006
DOI: 10.1103/physrevlett.97.193901
|View full text |Cite
|
Sign up to set email alerts
|

Interaction-Induced Localization of Anomalously Diffracting Nonlinear Waves

Abstract: We study experimentally the interactions between normal solitons and tilted beams in glass waveguide arrays. We find that as a tilted beam, traversing away from a normally propagating soliton, coincides with the self-defocusing regime of the array, it can be refocused and routed back into any of the intermediate sites due to the interaction, as a function of the initial phase difference. Numerically, distinct parameter regimes exhibiting this behavior of the interaction are identified.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, when the tilt angle is in the SD regime of the right beam (Fig. 4(d)), the instability (strong attraction between the beams) is extended for phase differences far beyond a vicinity of 2π multiplies [10]. Remarkably, the SD beam can be routed as a localized DS into any intermediate site, with the appropriate phase difference, while the normally propagating DS is partially annihilated.…”
Section: Discrete-soliton Interactions In Nonlinear 1d Waveguide Arraysmentioning
confidence: 99%
See 3 more Smart Citations
“…However, when the tilt angle is in the SD regime of the right beam (Fig. 4(d)), the instability (strong attraction between the beams) is extended for phase differences far beyond a vicinity of 2π multiplies [10]. Remarkably, the SD beam can be routed as a localized DS into any intermediate site, with the appropriate phase difference, while the normally propagating DS is partially annihilated.…”
Section: Discrete-soliton Interactions In Nonlinear 1d Waveguide Arraysmentioning
confidence: 99%
“…At high input power (Fig. 4(b)), nonlinear instability occurs around multiplies of ∆θ = 2π, which partially diverts the beams into the intermediate sites [8][9][10][11]. As tilts are imposed on the right DS, Figs.…”
Section: Discrete-soliton Interactions In Nonlinear 1d Waveguide Arraysmentioning
confidence: 99%
See 2 more Smart Citations
“…Iwanow et al [31] reported another GS in the [-π ,π ] range on periodically-poled lithium niobate; agreement with CMT was correct both on the deviation and on the divergence variations, but using a mere adjustable coupling coefficient. Two other articles have reported GSs involving soliton formation [32] or interface modes [30].…”
Section: Probing the Band Structurementioning
confidence: 99%